FORMULATION DESIGN AND EVALUATION OF LORATADINE AND EXTENDED RELEASE PHENYLEPHRINE HYDROCHORIDE TABLETS - JAYADEV PATIL,; VISHWAJITH V,; GOPAL.V, (International Journal of Pharma and Bio Sciences, 2014)
In the present work Loratadine and Phenylephrine Bilayer tablets were prepared by compressing Loratadine layer as direct compressible layer which is an immediate release layer and Phenylephrine hydrochloride by wet granulation method as sustained release layer which are compressed using Bilayer tableting machine. The tablets were evaluated for thickness, hardness, friability, and weight variation. In vitro dissolution studies were performed using USP apparatus –II (paddle method) in 900ml of 0.1N HCl at 50 rpm. The physical properties of the tablets did not show any significant variations and were found to have good physical integrity. Tablets with Loratadine layer containing Lactose DCL21, PG Starch showed better release and the Phenylephrine Hydrochloride layer containing DCP(21.6%), Natrosol (5%), HPMC K15M(10%) emerged as the overall best formulation based on the in-vitro drug release studies. Short term stability studies on the formulations indicated that there are no significant changes in drug content and drug release profile. Among all the formulations Trial 6 emerged as the overall best formulation found to be promising